2019
DOI: 10.1111/ecc.13134
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacy linked to engagement and psychological benefits among breast cancer survivors in Internet‐based peer support groups

Abstract: Objective Internet‐based peer support groups (ISGs) represent an innovative, scalable approach to addressing information and support needs of cancer survivors. However, this innovation may not benefit survivors equally due to population variance in digital literacy. This study examined how digital literacy influences level of engagement in and psychological benefits from participating in ISGs for breast cancer (N = 183). Methods Secondary analysis of data from a randomised trial of ISGs that included behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…However, as noted in our main study ( Nissen et al, 2020 ), higher age was associated with attrition. In addition to age and educational level, it could, therefore, in future studies be relevant to consider computer literacy, which has previously been found to be associated with both older age and lower educational level, as well as with treatment response ( Lepore et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as noted in our main study ( Nissen et al, 2020 ), higher age was associated with attrition. In addition to age and educational level, it could, therefore, in future studies be relevant to consider computer literacy, which has previously been found to be associated with both older age and lower educational level, as well as with treatment response ( Lepore et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent meta-analysis, older mean sample age was associated with smaller effects ( Cillessen et al, 2019 ), which is also what was found in a previous study of an online Mindfulness-Based Cancer Recovery program, delivered in groups via video conference ( Zernicke et al, 2016 ). A study investigating computer literacy and participation in online support groups for cancer patients found that older participants with lower levels of education had lower levels of digital literacy and experienced less improvement in psychological distress, compared with younger participants with higher levels of education ( Lepore et al, 2019 ). Generally, older age has been found related to lower levels of psychological distress in cancer patients ( Linden et al, 2012 ; Götze et al, 2020 ), and, due to floor effects, thus older age could also be associated with smaller effects.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise, for instance, increases the free tryptophan available for 5-HT synthesis (Chaouloff, 1997). Anxiety and/or depressive symptoms have also been attenuated by group-delivered cancer parenting programs and internet-based peer support groups (Lepore et al, 2019;Lewis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, large segments of the population, including older adults, patients with lower education or socioeconomic status, and those with low digital literacy, are likely not being served by online support communities. 10,21 It is important for people involved in developing digital information and support tools to ensure that these patients are not left out.…”
Section: Community Sustainabilitymentioning
confidence: 99%